2019
DOI: 10.3390/nu11020299
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neuroinflammation and Improved Functional Recovery after Traumatic Brain Injury by Prophylactic Diet Supplementation in Mice

Abstract: Currently, there are no approved therapeutic drugs for the treatment of traumatic brain injury (TBI), and new targets and approaches are needed to provide relief from the long-term effects of TBI. Recent studies suggest that nutrition plays a critical role in improving the outcome from TBI in both civilians and military personnel. We have previously shown that GrandFusion® (GF) diets improved recovery from cerebral ischemia and enhanced physical activity and endurance in rodent models. We, therefore, sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…As previous studies have shown, the APP/PS1 mice used in these experiments started to demonstrate increased levels of A peptides and presence of amyloid plaques in the brain at about 3–4 months of age. This increase of amyloid load or oligomerization was connected with both GFAP-positive astrocytes and CD-68-positive microglia in the cortex area and the hippocampal region [ 18 , 24 ]. Therefore, 3- to 4-month-old APP/PS1 mice display early phases of AD-like pathology and were designated for testing GF diet intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As previous studies have shown, the APP/PS1 mice used in these experiments started to demonstrate increased levels of A peptides and presence of amyloid plaques in the brain at about 3–4 months of age. This increase of amyloid load or oligomerization was connected with both GFAP-positive astrocytes and CD-68-positive microglia in the cortex area and the hippocampal region [ 18 , 24 ]. Therefore, 3- to 4-month-old APP/PS1 mice display early phases of AD-like pathology and were designated for testing GF diet intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 3- to 4-month-old APP/PS1 mice display early phases of AD-like pathology and were designated for testing GF diet intervention. Furthermore, these mice show a significant escalation in amyloid load and memory impairment at 6 to 8 months of age [ 18 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations